Geological storage of nuclear wastes: Insights following the Fukushima crisis - Gallardo, Adrian Hugo (2014)
The geological storage of high-level nuclear wastes (HLW) has been in the agenda of Japan for several years. Nevertheless, all the research can become meaningless without understanding the public feelings about the disposal. The events at Fukushima in 2011 altered the perception towards nuclear-waste storage in the country. This work investigates the attitude of young Japanese towards the construction of a repository following the Fukushima crisis, and examines how public perception changed after the event. A survey among 545 university students from different regions of Japan addressed three main variables: dread, trust and acceptance. The results suggest that the economy of the country is still the most concerning issue, but there was a dramatic increase of attention towards everything "nuclear". Radiation leakage and food contamination are major concerns as well. The distrust towards the government deepened after Fukushima, although more than half of the respondents would accept the repository. In a clear phenomenon of NIMBY (not in my back yard), the acceptance drops to less than 20% if the repository is to be installed near the respondents´ residency. Financial incentives would increase the acceptability of the siting, although only a substantial compensation might minimise the NIMBY in potential host communities.